2019
DOI: 10.1038/s41598-019-44213-3
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus induces DNA damage in host cell

Abstract: Staphylococcus aureus causes serious medical problems in human and animals. Here we show that S. aureus can compromise host genomic integrity as indicated by bacteria-induced histone H2AX phosphorylation, a marker of DNA double strand breaks (DSBs), in human cervix cancer HeLa and osteoblast-like MG-63 cells. This DNA damage is mediated by alpha phenol-soluble modulins (PSMα 1–4 ), while a specific class of lipoproteins (Lpls), encoded on a pathogenicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 67 publications
1
32
0
1
Order By: Relevance
“…Moreover, it was suggested that early activation of NLRP3 (Ip et al, 2010;Sokolovska et al, 2013) inflammasomes is triggered by events, such as the production of ROS, that are associated with the phagocytic process in macrophages (Sokolovska et al, 2013). Recently, we demonstrated that S. aureus induces the production of ROS in WT MG-63 cells (Deplanche et al, 2019). We hypothesize that S. aureus-induced ROS plays a similar role in inflammasome activation in non-phagocytic cells.…”
Section: βmentioning
confidence: 80%
See 4 more Smart Citations
“…Moreover, it was suggested that early activation of NLRP3 (Ip et al, 2010;Sokolovska et al, 2013) inflammasomes is triggered by events, such as the production of ROS, that are associated with the phagocytic process in macrophages (Sokolovska et al, 2013). Recently, we demonstrated that S. aureus induces the production of ROS in WT MG-63 cells (Deplanche et al, 2019). We hypothesize that S. aureus-induced ROS plays a similar role in inflammasome activation in non-phagocytic cells.…”
Section: βmentioning
confidence: 80%
“…To persist within the host cells, S. aureus also developed strategies to circumvent the host cell defenses (Alekseeva et al, 2013;Deplanche et al, 2015;Deplanche et al, 2016;Deplanche et al, 2019). Here we aimed to investigate the contributions of internalized S. aureus on alteration of host defense events such as inflammasomes activation and bacterial clearance in infected osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations